New Bioactive Sesquiterpeniods From the Plant Endophytic Fungus Pestalotiopsis theae - Liu, Gaoran; Huo, Ruiyun; Zhai, Yanan; Liu, Ling (Frontiers in Microbiology, 2021)
Three new secondary metabolites pestalothenins A–C (1–3), including two new humulane-derived sesquiterpeniods (1 and 2) and one new caryophyllene-derived sesquiterpeniod (3), together with five known compounds (4–8) were isolated from the crude extract of the plant endophytic fungus Pestalotiopsis theae (N635). Their structures were elucidated by the extensive analyses of HRESIMS and NMR spectroscopic data. The absolute configurations of 1–3 were determined by comparison of experimental and calculated electronic circular dichroism (ECD) spectra. The cytotoxic effects of these compounds were evaluated in vitro. Compound 6 showed moderate cytotoxicity against T24 and MCF7 cell lines. In addition, compounds 1–8 were also evaluated for antibacterial activity.